Knowledge Management of Education Institutions According to The Views of Administrators and Teachers under The Saraburi Primary Educational Service Area Office1 - lapcharoen, supawadee; Pachanavon, Apison; Sriraksa, Pratoom (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2023)
The objectives of this research were 1. to study knowledge management of educational institutions according to the perspectives of administrators and teachers of the Saraburi Primary Education Service Area Office 1, and 2. to compare knowledge management of educational institutions according to the perspectives of administrators and teachers of the Saraburi Primary Educational Service Area Office 1 classified by personal factors. The sample groups used in this research were 316 samples who were administrators and teachers of the Saraburi Primary Educational Service Area Office 1 and were randomized with the use of stratified random sampling method. The instrument used in data collection for this time was a questionnaire with a confidence value of 0.939. The statistics used for data analysis were percentage, mean, standard deviation and t-test. One-way ANOVA Subsequent pairwise comparison using the Chef’s formula. The results showed that 1. knowledge management of educational institutions according to the views of administrators and teachers under the office Saraburi Primary Educational Service Area Area 1, in overall and in each aspect, were at a high level in all 4 aspects, arranged in descending order of averages as follows: 1) knowledge acquisition 2) knowledge creation 3) transfer knowledge and utilization and 4) knowledge collection and retrieval, 2. comparison of knowledge management according to the views of administrators and teachers of the Saraburi Primary Educational Service Area Office 1, the overall classification, classified by position, educational background, academic standing, differed statistically at .05 level, while experience in position, training, and size of educational institution had no different statistically significant at the .05 level.